1984
DOI: 10.1159/000124012
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline and Prostaglandin E<sub>2</sub> Stimulate LH-RH Release from Rat Median Eminence through Distinct 1-Alpha-Adrenergic and PGE<sub>2</sub> Receptors

Abstract: Noradrenaline (NA) and prostaglandin (PG) E2 produced a dose-related stimulation of luteinizing hormone releasing hormone (LH-RH) release from incubated median eminence of adult male rats, with ED50 values of 6.10–7 and 8.10–8 M, respectively. The effects of some adrenoceptor agonists (10^5M) on LH-RH release were tested: only phenyleph-rine (α1-agonist) stimulated LH-RH release; clonidine (α2 > α1-agonist) and isoproterenol (β-agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…That the interaction of NPY and LHRH may be of physiological significance is also suggested by our observation that the potency of NPY in stimulating basal LHRH release (submicromolar to mi cromolar range) is comparable to other known excitatory neurochemicals, such as NE [16, 28. 31] or prostaglandin E: [16,30,31] for which the evidence of physiological involve ment in LH secretion has been presented [17,21], It remains to be determined how the ovarian steroid mi lieu alters the responses of LHRH neurons to stimuli from another peptidergic system, such as seen in the case of NPY. The facilitatory response due to steroids may involve changes in NPY reception or in signal transduction subseq uent to binding to receptors, as well as effects on the availa ble pool of LHRH as a result of augmented synthesis and processing of LH RH [8,9, 17, 23-25, 33, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the interaction of NPY and LHRH may be of physiological significance is also suggested by our observation that the potency of NPY in stimulating basal LHRH release (submicromolar to mi cromolar range) is comparable to other known excitatory neurochemicals, such as NE [16, 28. 31] or prostaglandin E: [16,30,31] for which the evidence of physiological involve ment in LH secretion has been presented [17,21], It remains to be determined how the ovarian steroid mi lieu alters the responses of LHRH neurons to stimuli from another peptidergic system, such as seen in the case of NPY. The facilitatory response due to steroids may involve changes in NPY reception or in signal transduction subseq uent to binding to receptors, as well as effects on the availa ble pool of LHRH as a result of augmented synthesis and processing of LH RH [8,9, 17, 23-25, 33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that NPY may mo dulate LHRH release either directly, or indirectly, by chan ging the catecholamine input to the LHRH neurons in the hypothalamus. Therefore, the objectives of the present studies were to test whether NPY, like NE [7,16,28,31], can stimulate in vitro release of LH RH from the nerve terminals of the median eminence and whether the direction of the LHRH response, as implied by in vivo studies [18], is de pendent upon ovarian hormone pretreatment. Addi tionally, these studies evaluated the effects of NPY on the in vitro release of NE and dopamine (DA) simultaneously with LHRH.…”
mentioning
confidence: 99%
“…A detailed pharmacological analysis, which was carried out on a culture of the interstitial Cells of the testes of mice, showed that the production of androgens is activated only after the stimulation of the ~2-adrenoreceptors, which according to our data, do not participate in sexual activation. Consequently, it can be held that in our experiments the adrenoblockers exerted an effect at the level of the hypothalamus, since ~l-adrenoreceptors which participate in the regulation of the secretion of luliberin have been found in the median eminence of rats [13]. In addition, it was shown that the administration of prazosin does not have an influence on the increase in the T level in the blood of rats induced by chorionic gonadotropin [9].…”
Section: Resultsmentioning
confidence: 46%
“…On the other hand, the release of immunoreactive GnRH in vitro from the rat hypothalamus can be stimulated by potassium [22][23][24], ATP and magnesium [25], prostaglandin E? [22,26,27], dopamine [24,28], and norepi nephrine [26,28,29], Whether the regula tion of T4 on the release of GnRH reflects a direct effect on hypothalamic GnRH neu rons or an indirect effect through catechol amine turnover or influx of ions is unknown. Our data do not rule out the possibility that other hypothalamic agents can influence the release of LH as well.…”
Section: Discussionmentioning
confidence: 99%